Childhood versus adult-onset systemic lupus erythematosus: long-term outcome and predictors of mortality. Issue 2 (February 2017) - Fatemi, Alimohammad; Matinfar, Mohammad; Smiley, Abbas
Abstract The aim of this study was to compare survival of childhood-onset systemic lupus erythematosus (c-SLE) and adult-onset SLE (a-SLE) according to initial manifestations. This was a retrospective cohort study. All patients were categorized into c-SLE (≤18 years) and a-SLE (>18 years). The clinical and serological data at the time of diagnosis were recorded and compared. Kaplan-Meier curves were used to compare survival rates between the two groups. Predictors of mortality were obtained by a backward Cox regression. One hundred eighty patients with c-SLE and 394 patients with a-SLE were enrolled. The female/male ratio was higher in c-SLE (P = 0.0001). Lupus nephritis (P = 0.002) and valvular heart disease (P = 0.025) were more common in c-SLE and a-SLE, respectively. In a 23-year follow-up, 20 patients (11.1%) with c-SLE and 35 patients (8.9%) with a-SLE died. Mortality was not significantly different between them (P = 0.4). The main causes of death were nephritis (50% in c-SLE vs. 29% in a-SLE), infections (40% in c-SLE vs. 29% in a-SLE), and circulatory disease (10% in c-SLE vs. 37% in a-SLE). The difference was not significant (P = 0.08). Cumulative survival rates after 5, 10, 15, and 20 years were 91, 87, 85, and 78% in c-SLE and 93, 90, 90, and 83% in a-SLE, respectively. By multivariate analysis, seizure, proteinuria, and nephritis in c-SLE and seizure, hematuria, and pericarditis in a-SLE had negative prognostic effect on survival. Both c-SLE and a-SLE patients with seizure or renal involvement should be monitored more carefully to prevent ominous outcomes.